Comparative evaluation of remineralization potential of casein phosphopeptide-amorphous calcium phosphate and casein phosphopeptide-amorphous calcium phosphate fluoride on artificial enamel white spot lesion: An in vitro light fluorescence study - R Mehta; B Nandlal; S Prashanth (Wolters Kluwer Medknow Publications, 2013)
Background: World-wide, the contribution of dental caries to the burden of oral diseases is about 10 times higher than that of periodontal disease, the other common oral condition. Owing to its globally high prevalence, dental caries is a "pandemic" disease characterized by a high percentage of untreated carious cavities causing pain, discomfort and functional limitations. Untreated carious cavities; furthermore, have a significant impact on the general health of children and on the social and economic well-being of communities. A surgical approach to the elimination of carious lesion was developed a century ago; this approach was necessary at that time, because there was no valid alternative. The focus in caries has recently shifted to the development of methodologies for the detection of the early stages of caries lesions and the non-invasive treatment of these lesions. The non-invasive treatment of early lesions by remineralization has the potential to be a major advance in the clinical management of the disease. Remineralization of white-spot lesions may be possible with a variety of currently available agents containing fluoride, bioavailable calcium and phosphate and phosphate. This concept bridges the traditional gap between prevention and surgical procedures, which is just what dentistry needs today. Aims and Objectives: The aim of this in vitro study was to evaluate and to compare the remineralization potential of casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) and casein phosphopeptide-amorphous calcium fluoride phosphate (CPP-ACFP) on artificial white spot enamel lesions using the quantitative light fluorescence (QLF). Materials and Methods: A total of 45 caries-free extracted maxillary first premolars were embedded in acrylic resin. The samples were randomly divided into three groups namely control group, CPP-ACP group and CPP-ACFP group with 15 samples in each group. The samples of each group were subjected to demineralization process for a period of 96 h. The samples were then mounted in the artificial mouth model and subjected to remineralization and pH cycling for a period of 21 days. QLF readings were recorded at the end of demineralization (1 st , 7 th , 14 th and 21 st day) and were statistically analyzed. Results: As compared with artificial saliva both CPP-ACP and CPP-ACFP produced significant amount of remineralization of the artificial enamel white spot lesion (P < 0.001), however when the remineralizing effect of CPP-ACP was compared with the remineralizing effect of CPP-ACFP there was no significant difference. Significant amount of remineralization was produced by CPP-ACP and CPP-ACFP only after the 7 th day. After the 14 th day, the remineralization produced by both CPP-ACP and CPP-ACFP as compared to artificial saliva was non-significant.